A Review of Social Innovation Initiatives in Malaysia (Journal of Science, Technology and Innovation Policy, 2021)
Social innovation is becoming increasingly recognised as a solution for social challenges which the conventional government policy approach or market are unable to address. Social innovation is defined as a new solution that simultaneously meets social needs more effectively than the existing solutions, and leads new and improved capabilities and relationships. It also allows assets and resources to be improved in a better manner. In other words, it has a positive impact on society, as it enhances the capacity to act. Despite the fact that it is an emerging field in Malaysia, making the term ‘social innovation’ a recent articulation in public policies, several existing initiatives have been carried out by various government ministries and agencies as well as the third sector entities that successfully adopted the social innovation approach in addressing society’s needs. Thus, this paper aims to review the implementation of socially innovative initiatives in Malaysia that promote the socio-economic well-being of the society, particularly low-income and marginalised groups. The findings demonstrate that there are four main forms of social innovation initiatives for socio-economic well-being in Malaysia, namely, i) microfinancing; ii) social entrepreneurship; iii) public service delivery and; iv) grassroots innovation (science and technology-based). This paper concludes that several social innovation initiatives in Malaysia have shown substantial improvement in uplifting the socio-economic well-being of the people, and have had considerable support from the government as well as the third sectors. Nonetheless, to ensure a greater impact by the initiatives, extra attention should be offered to provide a sufficient and comprehensive enabling environment with equal supply and demand side measures, as there exists a lack of a clear and coordinated social innovation framework in Malaysia. Furthermore, there is a need to conduct further research on grassroots social innovation in supporting the national STI Policy, as there is a lack of government reports and studies that have been done to analyse the socio-economic impact of the initiatives.
Keywords: Social Innovation; Innovation; Social Entrepreneurship; Policy; Malaysia